Detection of Elements Present in Leaves of Tanner’s cassia. - A. GAIKWAD, SUCHETA; A. KALE, ASHA; S. MUNDHE, KAVITA; DESHPANDE, N.R.; P. SALVEKAR., JYOTI (Asian Journal of Chemistry, 2010)
Cassia auriculata (L) commonly konown as Tanner's cassia is a medicinal plant which grows abundantly all over India. It is widely used in Ayurvedic medicine as tonic, astringent and remedy for dibeties, conjectives and opthalmia. Leaves of Cassia auriculata L are useful in chronic fever, anthelmintic. The metals content of Cassia auriculata leaves was carried out. It was found that potasium, calcium, magnesium, manganese, iron, zinc along with copper, phosphorous. Quantities of calcium, sodium, copper were found negligible in it but iron, zinc, magnesium, manganese are the potential source.